African traditional beer: changing organization and spaces of South Africa's sorghum beer industry. Issue 3 (3rd July 2019) - Rogerson, Christian M.
ABSTRACT: Scholarship on the geographies of beer is concentrated mainly in the global North. Sub-Saharan Africa is the most undeveloped region in terms of international beer focused research. This neglect must be set against the growing attention on the region by the world's leading brewing enterprises. Within beer research geographies, one distinctive facet of Africa's beer economy is the manufacture of a variety of traditional or indigenous beers which are quite unlike the barley based clear beers and multiplying varieties of craft beers as consumed in the Global North. Indigenous beers formed an important part of the rural African social fabric and undertaken by mainly women brewers. The objective here is to address the limited extant knowledge about fermentation geographies of Africa. The focus is on South Africa's sorghum beer industry and the commodification of traditional beer, interrogating the changing organization and associated spaces of production of this sector. Using archival sources and the industry press two historical phases are unpacked in the chequered development of the sorghum beer industry in South Africa. The study demonstrates the shrinking spaces of production of the formal economy of sorghum beer as the industry moved from serving narrow localized markets to concentrated production for wider regional and national markets. Arguably, recent struggles surrounding the ownership and control of South Africa's sorghum beer industry represent an integral facet of the increasingly competitive economic landscape of beer across contemporary sub-Saharan Africa.